Isolation and Characterization of Carbofuran degrading Bacteria from Malaysia Soil - Abdul Rahman, Sukirah (2005)
Carbofuran degrading bacteria were isolated from the soil sample. Isolate 7 was isolated from the soil sample collected from the Marriot Hotel car park in Johor Bahru. The sampling location is known to have no history of carbofuran application or contamination. The Preliminary screening of the MTT (3-[4, 5-dimethylthiazol-2-yl]- ,diphenyltetrazoliumbromide) assay screened 148 isolates based on the measurement of growth respiration of the isolated bacteria. Seven isolates as well as Isolate 2,7, 9, 13, 2 1, 72 and 138 are shown to have the highest absorbance measured by the assay. These isolates were selected from the blue colour formation of formazan. Selected isolates were subjected to Secondary screening which included the MTT Assay and Direct Plate Count method. Five isolates; Isolate 2, 7, 9, 13 and 21 were chosen from the highest colony count in CFUI mL and highest absorbance obtained from the MTT assay. The High Performance Liquid Chromatography was used as the detector for the carbofuran degrader which was the Isolate 7. In this study, Isolate 7 gave the reading of 92.98% degradation of 100mgIL carbofuran in the enrichment culture on sixth day of the incubation period. This followed by Isolate 13 which gave the measurement carbofuran degradation reading of 55.8 %, Isolate 21; 54.09 %, and Isolate 9; 53.6%. The lowest degradation was measured from Isolate 2 with 33.6 % of carbohan degradation. The control without bacteria accounted only 13 % degraded carbofuran suggesting the carbofuran underwent chemical degradation. The optimum growth conditions were determined for Isolate 7 based on the highest colony count (CFUImL) of the bacteria on nutrient agar. Glucose as a carbon source and 60 mg/L of carbofuran, in carbofuran enrichment culture were used as optimum parameters for the growth of Isolate 7. The optimum pH of c a r b o h enrichment culture was at pH 7 and the optimum temperature was at 25"C, at room temperature. In the designed optimize conditions, the carbofuran degradation of Isolate 7 was two days earlier, which is at 93.05% degradation on the fourth day. Isolate 7 was tentatively identified as Bacillus sp. based on the morphological characterization and biochemical test. The carbofuran degrading enzyme for carbofuran showed the Km value of 0.9571 m M a,nVd at 0.1142 mmole min-' Optimum temperature for the enzyme activity was in the range of 40°C to 45°C and pH was in the range of 8 to 10. The Native PAGE and SDS PAGE showed a lot of protein bands appeared suggesting that the protein was still not purified and several steps must be done to remove the impurities.